Dealing with the facts of life: the management of intra-party factionalism in the Iberian radical left parties - Lourenço, Pedro (2024)
Factionalism is an important element in parties' internal life, affecting their policies, strategies, electoral performance and even survival. Yet little is known about how parties manage factionalism. This study examines how radical left parties (RLPs) manage factionalism, drawing on a comparative case study of four RLPs – the Spanish Podemos and United Left (IU), and the Portuguese Left Bloc (BE) and Communist Party (PCP) – from 2010 to 2019. Drawing on original data collection, we find that parties adopt both formal and informal mechanisms to address factionalism. However, their approaches differ significantly. We identify two main approaches towards factionalism: a permissive approach, which allows internal pluralism, in the BE and IU; and a prohibitionist approach, which actively fights factionalism, in Podemos and the PCP, with competitive prohibitionism in the former and pre-emptive prohibitionism in the latter. These approaches strongly correlate with parties' origins and political orientation, but neither fully prevents intra-party conflict or splintering.